Treatment of relapse of small cell lung cancer in selected patients with the initial combination chemotherapy carboplatin, etoposide, and epirubicin. Issue 5 (May 1992) - Collard, P; Weynants, P; Francis, C; Rodenstein, D O
Abstract : BACKGROUND: Relapse of small cell lung cancer is not usually treated with further chemotherapy as results are considered to be disappointing. METHODS AND RESULTS: Six patients with relapse of small cell lung cancer after a complete initial response and remission of more than one year responded to repeat treatment with the initial chemotherapy comprising carboplatin, etoposide, and epirubicin. The second remission ranged from six months to more than 15 months. CONCLUSION: In patients with a relapse of small cell lung cancer after a complete initial response and prolonged remission retreatment with the initial combination chemotherapy cannot be dismissed and requires further study.